Mass media: a new language - Yelo Diaz, Soledad (CIC. Cuadernos de Información y Comunicación, 2017)
Mass media, in their analogical or digital versions, from printed paper to the web, are reinterpretations of the communicative systems that constitute their basis: the written language and the audivosual language, which being used for communicating in a public sphere, have a new dimension thoroughly analysed by now. But we can go farther. The communicative evolution of the media allows us to discover some evolutioned and systemic forms of narrative and argumentation, a most singular oral and written linguistic system in a broader sense, which has muted and now it is developing a brand new grammar, not specialized or formalized but different: a new language. In it all the structural elements define a communicative system in an autonomous development. ¿A new language for what? Because mass media do not reflect only the same referential world, but they transmit themselves and the reality that they mythologise, the actuality.
Keywords: Mass media; metatext; modus operandi in journalism; routines in journalism; informative and audiovisual grammar; actuality; myth creation; structure of information system.